Lavado de dinero y corrupción: necesidad de mayor investigación para un sustento empírico sólido (2021)
This article analyzes the scientific literature on money laundering and corruption produced during the last fifteen years. Specifically, the article presents the main findings, consensus and knowledge gaps in the literature on the definitions and categories of money laundering and corruption, and the legislative, legal and political initiatives aimed at fighting them, including initiatives from the private sector or involving international cooperation. The article finds that, although there are multiple consensus regarding the political, economic and social impact of money laundering and corruption and the need to undertake a multidimensional fight against these crimes, including the private sector, there are substantial difficulties related to real understanding of the sociocultural and institutional factors and the political economy incentives or transnational capital flows that would help to understand the complexity of how these crimes occur in practice. This is a pressing concern, since policies are being implemented without a solid empirical support.